2021
DOI: 10.1016/j.dyepig.2020.108955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the donor units on the properties of fluorinated acceptor based systems

Abstract: A new series of monomers in the donor-acceptor-donor array, namely 5-fluoro-4,7-di(furan-2-yl)benzo [c][1,2,5] thiadiazole (F 2 BT-F), and 5-fluoro-4,7-di(selenophen-2-yl)benzo [c][1,2,5] thiadiazole (S 2 BT-F), bearing 5-fluorobenzo[c][1,2,5]-thiadiazole as the acceptor moiety and furan and selenophene as the electron donating groups was synthesized and polymerized electrochemically. To compare heteroatom effect, thiophene analogue of newly synthesized F 2 BT-F and S 2 BT-F namely, (5-fluoro-4,7-di(thiophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…This can be explained in terms of the aromaticity of the heterocycle, the aromaticity decreases when the heterocycle has larger chalcogen atoms that result in poor overlap with the diene carbon p z orbitals. [47,63,64] The same trend was detected for homopolymers containing the electron-deficient spacers, HPOx and HPTzC2, the substitution of oxazole for thiazole, lead to a bathochromic shift of 39 nm in solution and 17 nm in thin film. In addition, a blueshift in the absorbance maxima 𝜆 max in solution and thin film, as well as, an increase in the vibronic shoulder of the solidstate was detected between HPTzC5 and HPTzC2.…”
Section: Optical Propertiessupporting
confidence: 64%
“…This can be explained in terms of the aromaticity of the heterocycle, the aromaticity decreases when the heterocycle has larger chalcogen atoms that result in poor overlap with the diene carbon p z orbitals. [47,63,64] The same trend was detected for homopolymers containing the electron-deficient spacers, HPOx and HPTzC2, the substitution of oxazole for thiazole, lead to a bathochromic shift of 39 nm in solution and 17 nm in thin film. In addition, a blueshift in the absorbance maxima 𝜆 max in solution and thin film, as well as, an increase in the vibronic shoulder of the solidstate was detected between HPTzC5 and HPTzC2.…”
Section: Optical Propertiessupporting
confidence: 64%
“…Monomers and polymers undergo a blue shift in their electronic spectra with increasing fluorine atom substitution on the BT unit, due to deviation from planarity upon fluorination. In this regard, they further synthesized two new D–A–D-type monomers utilizing 5-fluorobenzo[ c ][1,2,5]-thiadiazole as the acceptor unit 23 and furan and selenophene as the donor units. As prepared fluorinated polymers possess a low band gap (1.62–1.68 eV) and exhibit electrochromic properties with relatively low switching times.…”
Section: Introductionmentioning
confidence: 99%
“…PDT6FBT exhibited comparative values at all three wavelengths with a range value of 86–97 cm 2 C −1 . The above electrochromic performance demonstrated that PDT6FBT was on a par with its analogues PT2BT-1F (thiophene as terminal groups), PF2BT-F (furan as terminal groups), PS2BT-F (selenophene as terminal groups), and PE2BTD-F (EDOT as terminal groups) [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 , 33 ]. Önal et al reported 5-fluoro-2,1,3-benzothiadiazole-based ECPs [ 34 , 35 , 36 ], and analyzed the influence of a fluorine atom on the optical and electrical properties of a conjugated polymer. As we all know, alkyl side chains influence the redox behavior and electrochromic properties of the electrodeposited polymers [ 24 , 37 ].…”
Section: Introductionmentioning
confidence: 99%